Production of Activated Carbon from Natural Sources for Water Purification - Rizka Alfi Fadhilah Lubis; Hafni Indriati Nasution; Moondra Zubir (Universitas Negeri Medan, 2020)
Activated carbon as one of the widely used adsorbent has many application in the environment for the water purification and removing pollutant. Activated carbon can produced from agricultural waste and has not been optimally used. In this paper, these natural sources from agricultural waste materials has been reviewed and the potential as activated carbon. Characteristics of activated carbon that can be used as a activated carbon depends on surface area and pore structure prepared through activation method. Activation method for carbon depends on the precursor and characteristic of activated carbon which are expected. Natural sources can be converted into activated carbon by chemical, physical, or physical-chemical activation. Therefore, this paper is aimed to providing information about methods of production activated carbon has been reported for purify water.